Cement filled with phosphorescent materials for pavement: Afterglow decay mechanism and properties. (17th May 2021) - Wang, Wentong; Sha, Aimin; Lu, Zhen; Yuan, Dongdong; Jiang, Wei; Liu, Zhuangzhuang
Highlights: The brightness uniformity of SLCCM was analyzed. The SLCCM with various LP contents have different hydration products. The surface brightness of SLCCM under different external environment was assessed via indoor experiments. How the comprehensive action mechanism affects the luminescence performance of SLCCM was studied. Abstract: Improving drivers' visibility in night time conditions are vital. Within such context, the use of self-luminescent cement-based composite materials (SLCCM) could represent an enhancement with regard to road safety. In this study, the influence of hydration and distribution of luminescent powder (LP) on the mechanical properties and brightness of SLCCM were analyzed by mechanical properties, XRD, heat of hydration and fluorescence microscopy (FM) tests, and the mechanism of brightness decay was summarized. Based on this, the initial brightness and afterglow properties of SLCCM, as well as the chemical stability were studied. The results indicate that the mechanical strengths of the SLCCM specimens firstly increase and then decrease with the increasing of LP content. Meanwhile, the SrAl2 O4 reacted with calcium hydroxide to produce abundant C-S-H when the content of LP was low, which was covered on the LP surface, thus limiting the effective luminous area. However, when the LP content was too high, LP would be hydrated first, SrAl2 O4 can be hydrolyzed to form SrAl4 O7 . With the increase in curing age, part of the hydration product Sr(OH)2 formed SrCO3 due to the effect of CO2, while the hydrolytic equilibrium between LP and cement could be reached with medium LP content. The efficient economical illumination time for SLCCM having higher initial brightness after irradiation are 30 min, while the lighting 60 min can reach 96.67% of the maximum initial brightness, and the optimal LP content range is 20–25 wt%. Results of road self-illumination materials will further promote the paving of self-luminous pavement, which contribute to reduce power consumption and improve the safety of road traffic.